Transmission dynamics of visceral leishmaniasis in the Indian subcontinent – a systematic literature review - Hirve, S; Boelaert, M; Matlashewski, G; Mondal, D; Arana, B; Kroeger, A; Olliaro, P (Public Library of Science, 2016)
BACKGROUND: As Bangladesh, India and Nepal progress towards visceral leishmaniasis (VL) elimination, it is important to understand the role of asymptomatic Leishmania infection (ALI), VL treatment relapse and post kala-azar dermal leishmaniasis (PKDL) in transmission. METHODOLOGY/ PRINCIPAL FINDING: We reviewed evidence systematically on ALI, relapse and PKDL. We searched multiple databases to include studies on burden, risk factors, biomarkers, natural history, and infectiveness of ALI, PKDL and relapse. After screening 292 papers, 98 were included covering the years 1942 through 2016. ALI, PKDL and relapse studies lacked a reference standard and appropriate biomarker. The prevalence of ALI was 4-17-fold that of VL. The risk of ALI was higher in VL case contacts. Most infections remained asymptomatic or resolved spontaneously. The proportion of ALI that progressed to VL disease within a year was 1.5-23%, and was higher amongst those with high antibody titres. The natural history of PKDL showed variability; 3.8-28.6% had no past history of VL treatment. The infectiveness of PKDL was 32-53%. The risk of VL relapse was higher with HIV co-infection. Modelling studies predicted a range of scenarios. One model predicted VL elimination was unlikely in the long term with early diagnosis. Another model estimated that ALI contributed to 82% of the overall transmission, VL to 10% and PKDL to 8%. Another model predicted that VL cases were the main driver for transmission. Different models predicted VL elimination if the sandfly density was reduced by 67% by killing the sandfly or by 79% by reducing their breeding sites, or with 4-6y of optimal IRS or 10y of sub-optimal IRS and only in low endemic setting. CONCLUSION/ SIGNIFICANCE: There is a need for xenodiagnostic and longitudinal studies to understand the potential of ALI and PKDL as reservoirs of infection.